BNIP3 in melanoma: isn’t it IRONic? - Mónica Vara-Pérez; Patrizia Agostinis (Molecular & Cellular Oncology, 2021)
Melanoma cells exploit mitophagy and hypoxia signaling to promote their growth. In a recent study, we found that loss of B-cell lymphoma 2 (BCL-2)/adenovirus E1B 19kDa protein-interacting protein 3 (BNIP3) curbed Hypoxia Inducible Factor 1 alpha (HIF-1α) levels and melanoma growth in vivo. Insufficient levels of BNIP3 boost iron-driven prolyl hydroxylase 2 (Phd2)-mediated degradation of HIF-1α by exacerbating nuclear receptor activator 4 (Ncoa4)-mediated ferritinophagy. Thus, BNIP3 promotes melanoma growth by controlling iron metabolism.